Spread of drought in Rajasthan during the 1987 south-west monsoon (MAUSAM, 2004)
The failure of south-west monsoon over the Rajasthan state during 1987, has once again resulted in wide spread drought in most part of state. Agricultural production especially, in dryland tracts has considerably decreased, during the year of worst drought during 15 years period (1981-95). Weekly reference evapotranspiration values were estimate by Penman Montheith method for determination of water balance. The year 1987 found to be severe or disastrous drought year at all the stations studied except at Fatehpur where it was a moderate drought year. Studies on the incidence and spread of drought over Rajasthan during the severe drought year 1987, revealed that drought condition originated first in southern region (Banswara) during the 26th week, spread in south-west direction (Jodhpur and Pali) during the 27th & 28th weeks and dissipated in a north-east direction movement (Fatehpur) in 39th week.